Prevalence, Modes Of Treatment, And Patients’ Satisfaction With Kidney Stone Disease Management At Hospital Universiti Sains Malaysia - Nouri, Ahmed Ibrahim Abdel Rahman (2018)
Kidney stones form by the precipitation or crystallization of minerals and urinary constituents. It is a common problem worldwide manifested with recurrent intermittent pain episodes, surgical interventions and medication consumption which affect the quality of life of the patients. This study aimed 1) - to assess the prevalence of kidney stone disease among patients admitted to Hospital Universiti Sains Malaysia (HUSM), 2) - to determine the characteristics of stones, modes of treatment, renal function and comorbid conditions, 3) - to explore the patients’ satisfaction with the management of kidney stones disease, the social aspects, perceptions, and how the disease affecting their quality of life.